2021
DOI: 10.3390/jmse9080867
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Global Warming on the Poleward Heat Transport by Non-Stationary Large-Scale Atmospheric Eddies, and Feedbacks Affecting the Formation of the Arctic Climate

Abstract: It is a well-known fact that the observed rise in the Arctic near-surface temperature is more than double the increase in global mean temperature. However, the entire scientific picture of the formation of the Arctic amplification has not yet taken final shape and the causes of this phenomenon are still being discussed within the scientific community. Some recent studies suggest that the atmospheric equator-to-pole transport of heat and moisture, and also radiative feedbacks, are among the possible reasons for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 64 publications
(103 reference statements)
0
1
0
Order By: Relevance
“…SKT is the temperature of a liquid or solid surface (Gong et al, 2017;Lee et al, 2017;Lesins et al, 2012), but SATL is the temperature of the air above the surface, and hence dynamic advection affects the SATL tendency (Holton & Hakim, 2012). Numerous studies have suggested that remote forcing, specifically atmospheric and oceanic poleward energy transport (PET), contributes to Arctic surface warming through delivering heat and moisture to the Arctic as a response to extra-polar circulation changes (Baek et al, 2020;Soldatenko, 2021;Sun et al, 2022;Yang et al, 2010). However, as argued by Stuecker et al (2018), extra-polar forcing contributes less to polar amplification than local mechanisms.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…SKT is the temperature of a liquid or solid surface (Gong et al, 2017;Lee et al, 2017;Lesins et al, 2012), but SATL is the temperature of the air above the surface, and hence dynamic advection affects the SATL tendency (Holton & Hakim, 2012). Numerous studies have suggested that remote forcing, specifically atmospheric and oceanic poleward energy transport (PET), contributes to Arctic surface warming through delivering heat and moisture to the Arctic as a response to extra-polar circulation changes (Baek et al, 2020;Soldatenko, 2021;Sun et al, 2022;Yang et al, 2010). However, as argued by Stuecker et al (2018), extra-polar forcing contributes less to polar amplification than local mechanisms.…”
Section: Summary and Discussionmentioning
confidence: 99%